The Influence of Communication, Team Work, and Organizational Commitment on Improving Employee Performance at PT Seroja Lukindo Lestari Surabaya - Cahya Dewi Anisah; I Putu Artaya (NAROTAMA UNIVERSITY, Indonesia, 2019)
The purpose of this research is to determine the relationship between communication, team work, and organizational commitment to the performance of employees at PT Seroja Lukindo Lestari Surabaya. This research is using quantitative method. The population and sample based on questionnaires to employees of PT Seroja Lukindo Lestari Surabaya of 67 respondents. The method of data collection uses interviews, observations and questionnaires. Analysis of the data used validity test, reliability test, classic assumption test and multiple linear analysis test. The results of the research showed Communication (X1), Team Work (X2), and Organizational Commitment (X3) had a significant relationship to employee performance (Y) which have a significant value <0.05.